Peptides Released from Foremilk and Hindmilk Proteins by Breast Milk Proteases Are Highly Similar - Nielsen, Søren D.; Beverly, Robert L.; Dallas, David C. (Frontiers in Nutrition, 2017)
Human milk contains active proteases that initiate hydrolysis of milk proteins within the mammary gland. Milk expressed at the beginning of feeding is known as foremilk and that at the end of feeding is known as hindmilk. As hindmilk contains higher fat, vitamins A and E, and higher calories than foremilk, feeding only hindmilk initially and reserving foremilk for later is practiced in some neonatal intensive care units. This study investigated the difference in peptide profiles, predicted milk protease activities, and bioactive peptides between foremilk and hindmilk. Bioactive peptides are short fragments of proteins that influence biological processes. Four mothers pumped 10 mL of their foremilk and 10 mL of their hindmilk into iced containers prepared with antiproteases and the samples were immediately frozen. The peptide profile of each sample was analyzed by liquid chromatography nano-electrospray ionization Orbitrap Fusion tandem mass spectrometry. Peptide abundance (sum of ion intensities) and count (number of unique peptide sequences) in each milk sample were determined from this analysis. The specific enzymes that participated in peptide release were predicted based on the amino acids positioned at each cleavage site. Peptide bioactivity was predicted based on homology to a known functional peptide database and two bioactivity prediction algorithms. Hindmilk contained a higher count of peptides than foremilk. The higher number of unique peptide sequences in hindmilk were related to hydrolysis of β-casein, osteopontin, αs1-casein and mucin 1 via plasmin and elastase cleavage, and possible aminopeptidase and carboxypeptidase activities. Though hindmilk contained a greater number of peptides than foremilk, the overall peptide abundance did not differ, and most of the total peptide abundance derived from peptide sequences that were present in both milk types. The presence of higher numbers of predicted bioactive peptides in the hindmilk could indicate that the practice of providing hindmilk rather than foremilk to premature infants could positively impact health outcomes; however, as there are few differences in overall peptide abundance, the overall effect is likely limited.